LITERATURE REVIEW: FRAUD AUDITING IN INDONESIA (International Journal of Innovative Technologies in Economy, 2023)
Financial statement fraud or corruption is one of the most common types of fraud committed by company executives. Pressure, opportunity, rationalization, arrogance, and the ability to commit fraud are all factors that contribute to financial statement fraud. The role of the auditor is critical in detecting signs of fraud in financial reports. Therefore, the researchers wish to conduct a literature review on audit fraud, focusing on the role of auditing in identifying fraudulent corporate financial statements in Indonesia. Auditors play a crucial role in detecting fraud in a financial report, according to the findings of this study, which the researchers hope will provide future researchers with insight and references for research in the field of fraud auditing and inform the public of this fact.